Sensitivity of mice to lipopolysaccharide is increased by a high saturated fat and cholesterol diet - Stevens Rachel L; Rose Jane L; Liu Tongzheng; Huang Hong; Hoyt Dale G (BMC, 2007)
Abstract Background It was hypothesized that a pro-atherogenic, high saturated fat and cholesterol diet (HCD) would increase the inflammatory response to E. coli endotoxin (LPS) and increase its concentration in plasma after administration to mice. Methods C57Bl/6 mice were fed a HCD or a control diet (CD) for 4 weeks, and then treated with saline, 0.5, 1 or 2 mg LPS/kg, ip. Liver injury (alanine:2-oxoglutarate aminotransferase and aspartate aminotransferase, collagen staining), circulating cytokines (tumor necrosis factor-α, interleukin-6 and interferon-γ), factors that can bind LPS (serum amyloid A, apolipoprotein A1, LPS binding protein, and CD14), and plasma levels of LPS were measured. The hepatic response was assessed by measuring vascular cell adhesion molecule (VCAM)-1, inducible nitric oxide synthase (iNOS) and signal transducer and activator of transcription-1 proteins, and VCAM-1 and iNOS mRNAs. Hepatic mRNA encoding the LPS receptor, Toll like receptor 4, was also determined. Results Two mg LPS/kg killed 100% of mice fed HCD within 5 d, while no mice fed CD died. All mice treated with 0 to 1 mg LPS/kg survived 24 h. HCD increased plasma alanine:2-oxoglutarate aminotransferase and aspartate aminotransferase, and the enzymes were increased more by LPS in HCD than CD mice. Induction of plasma tumor necrosis factor-α, interleukin-6, and interferon-γ by LPS was greater with HCD than CD. Hepatic VCAM-1 and iNOS protein and mRNA were induced by LPS more in mice fed HCD than CD. Tyrosine phosphorylation of signal transducer and activator of transcription-1 caused by LPS was prolonged in HCD compared with CD mice. Despite the hepatic effects of HCD, diet had no effect on the LPS plasma concentration-time profile. HCD alone did not affect circulating levels of plasma apolipoprotein A1 or LPS binding protein. However, plasma concentrations of serum amyloid A and CD14, and hepatic toll-like receptor-4 mRNA were increased in mice fed HCD. Conclusion HCD increased the sensitivity of mice to LPS without affecting its plasma level. Although increased serum amyloid A and CD14 in the circulation may inhibit LPS actions, their overexpression, along with hepatic toll-like receptor-4 or other factors, may contribute to the heightened sensitivity to LPS.